CAPILLAROSCOPY IN HEALTHY SUBJECTS OF DIFFERENT AGE - Pavlov-Dolijanovic, Slavica; Bogojevic, Milan; Pravilovic Lutovac, Dragana; Zlatkovic-Svenda, Mirjana; Markovic, Ana; Djokovic, Aleksandra; Radunovic, Goran (Medical Research, 2025)
Introduction: Capillaroscopy is a non-invasive diagnostic tool used to detect morphological abnormalities in the microcirculation. The assessment of capillaroscopic findings in healthy subjects is likely the area where controversies are most difficult to resolve. This review focuses on capillary architecture in healthy individuals across different age groups.Methods: A search was conducted in PubMed, MEDLINE, and Scopus using the following terms: capillaroscopy, healthy subjects, Raynaud’s phenomenon, microcirculation, and microvascular abnormalities. A total of 10 relevant articles were identified.Results: The shape of capillaries and the architecture of the nailfold microvascular network can vary significantly among healthy individuals. The most commonly observed abnormalities in this population include tortuosity, crossovers, homogeneously enlarged loops, neoangiogenic capillaries, and microbleeding. Less frequently, more unusualpatterns, such as ramified, bushy, or glomerular loops, may be observed. These atypical features require careful evaluation to avoid missing a potential underlying disease.Conclusion: This review critically examines capillaroscopy findings in healthy individuals, taking into account typical nail care practices and age-related changes. These insights may assist clinicians in distinguishing physiological variations from early signs of microvascular damage.
Keywords: capillaroscopy, healthy subjects, Raynaud’s phenomenon, microcirculation, microvascular abnormalities.